Web-based Creative Learning and Information System for Rebranding Christian Schools - Wahyudi; Dani Kusuma; Adi Winanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The decline in the number of prospective students entering private schools is due to weak school management, the quality of teacher human resources, and the declining reputation of the school. This research aims to rebrand the Christian school by providing a school management information system, a creative space for teachers and students as innovative learning resources and materials, and an open space for churches and parents. The subjects involved were 54 audiences. The data collection methods used were observation, documentation, and interviews. The instruments used are observation sheets, school data documentation guides, interview guides, expert assessment forms for the products developed, limited trial and broad trial assessment forms, and product implementation effectiveness tests with the T-Test one group design test. After the data was collected, it was analyzed using qualitative data analysis techniques. This research is a development research using 4D and ASSURE design. The results showed a significant difference in the average score of teacher creativity before and after using SIMaS-Rg. So, SIMaS-Rg Kreatif proved to be practical and effective. This research is expected to improve the quality of education in Christian schools and attract more students to enrol, thus supporting the revival and progress of Christian schools in this digital era.